A4NH food systems research informs major multi-lateral investment in new program to improve fruit and vegetable intake in low- and middle-income countries - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
A4NH research - a literature review, re-interpretation of data, and examination of consumption and supply of fruits and vegetables in seven countries - shaped priorities for the new program.